A PROGNOSIS OF WIND ENERGY POTENTIAL AS A POWER GENERATION SOURCE IN BASRA CITY, IRAQ STATE - Al-Hussieni, Amani J. Majeed (European Scientific Journal, ESJ, 2014)
In this study, wind energy potential of Basra, one southern Iraqi cities, was analyzed for the period of five years from 2004 – 2008. The statistical data of five years’ wind speed measurements of this city are used to find out the wind energy potential. Behind the meteorological data, Weibull distribution method is assessed to evaluate wind characteristics. Based on these data, it was indicated that the numerical values of the shape and scale parameters for Basra varied over a wide range. The yearly values of k (dimensionless Weibull shape parameter), ranged from 1.684 to 4.276 with a mean value of 2.9, while those of C (Weibull scale parameter), were in the range 3.5–8.509 m/s with a mean value of 4.862 m/s. Corresponding values for monthly data of whole year were found to be within the range 2.383–3.116 and 4.425–5.719 m/s, respectively related to k and C Weibull parameters. Results revealed that the highest and the lowest wind power potential are in June and December, respectively. It was also concluded that the site studied is not suitable for electric wind application in a large-scale. It was found that the wind potential of the region can be adequate for non-grid connected electrical and mechanical applications.